The Park and the city: analysis of the Ecological Park “Valdemar Salmeirão”, in the city of Birigui/SP - Zanateli, Jéssica Telles; Constantino, Norma Regina Truppel (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
Most Brazilian cities have developed disorderly and in little harmony with the natural landscape, especially in the valley bottoms. It is understood that harmonious integration with the environment is the way to the permanence of cities and the well-being of their inhabitants, besides being a way to solve the problems that affect the urban environment. Thus, strategies have been formed in favor of quality urban expansion. The creation of linear parks in valley bottoms (aiming at the integration between people, vegetation, and waterways) is a good intervention that culminates in quality spaces and quality of life in society. However, if these spaces are not used and are not properly maintained, they will not achieve their purpose and tend to be abandoned. This article aims to highlight the relationship between river and city, analyzing the issue of interventions in valley bottoms, having as a case study the Ecological Park "Valdemar Salmeirão" in Birigui-SP, verifying its state and its current appropriation, based on bibliographic, cartographic and photographic surveys that support and illustrate the area in question.
Keywords: Linear Park. Valley Bottom. Urban Voids.